Peran Karakteristik Individu Sebagai Salah Satu Penentu Peningkatan Kinerja Karyawan - Devi Ika Agustina; Aprih Santoso (Trunojoyo University of Madura, 2021)
This research is motivated by a decrease in targets and realization in 2019 at PT. Bitratex Industries Semarang. The purpose of this research is to analyze the factors that influence employee performance. Samples were taken by purposive sampling technique. Analysis tool with multiple linear regression, hypothesis testing (t, F and coefficient of determination) and model accuracy test. The results showed that there was a positive and significant effect of individual characteristics, organizational commitment, intrinsic motivation and supervision where the better the employee's performance will increase. For the work environment is well formed then it has no effect on employee performance. The value of the coefficient of determination of 0.616 means that individual characteristics, organizational commitment, intrinsic motivation, supervision and work environment can affect employee performance by 61.6% and the remaining 38.4% is influenced by other variables.